Shift in Clinical Profile of Hospitalized Pneumonia in Children in the Non-pharmaceutical Interventions Period During the COVID-19 Pandemic: A Prospective Multicenter Study - Rybak, Alexis; Ouldali, Naïm; Angoulvant, François; Minodier, Philippe; Biscardi, Sandra; Madhi, Fouad; Hau, Isabelle; Santos, Audrey; Bouvy, Emilie; Dubos, François; Martinot, Alain; Dommergues, Marie-Aliette; et al. (Frontiers in Pediatrics, 2022)
Non-pharmaceutical interventions (NPIs) against coronavirus disease 2019 were implemented in March 2020. These measures were followed by a major impact on viral and non-viral diseases. We aimed to assess the impact of NPI implementation in France on hospitalized community-acquired pneumonia (hCAP) frequency and the clinical and biological characteristics of the remaining cases in children. We performed a quasi-experimental interrupted time series analysis. Between June 2014 and December 2020, 8 pediatric emergency departments throughout France reported prospectively all cases of hCAP in children from age 1 month to 15 years. We estimated the impact on the monthly number of hCAP using segmented linear regression with autoregressive error model. We included 2,972 hCAP cases; 115 occurred during the NPI implementation period. We observed a sharp decrease in the monthly number of hCAP after NPI implementation (-63.0% [95 confidence interval, -86.8% to -39.2%], p < 0.001). Children with hCAP were significantly older during than before the NPI period (median age 3.9 vs 2.3 years, p < 0.0001), and we observed a higher proportion of low inflammatory marker status (43.5% vs 33.1%, p = 0.02). Furthermore, we observed a trend with a decrease in the proportion of cases with pleural effusion (5.3% during the NPI period vs 10.9% before the NPI, p = 0.06). NPI implementation during the COVID-19 pandemic led both to a strong decrease in number of hCAP cases but also a major shift in the clinical profile of children affected, which may reflect a change in pathogens involved.